Infection and Cancer: Global Distribution and Burden of Diseases - Jin-Kyoung Oh; Elisabete Weiderpass (Ubiquity Press, 2014)
Background: Infection is one of the main risk factors for cancer. Objectives: Epidemiology, pathogenesis, and disease burden of infection-related cancers were reviewed by infectious agents. Findings: Chronic infection with Epstein-Barr virus, hepatitis B and C viruses, Kaposi sarcoma herpes virus, human immunodeficiency virus (HIV) type 1, human papillomavirus (HPV), human T-cell lymphotropic virus type 1, 'Helicobacter pylori', 'Clonorchis sinensis', 'Opisthorchis' viverrini,and 'Schistosoma haematobium' are associated with nasopharyngeal carcinoma; lymphomaand leukemia, including non-Hodgkin lymphoma, Hodgkin lymphoma, and Burkitt lymphoma; hepatocellular carcinoma; Kaposi sarcoma; oropharyngeal carcinoma; cervical carcinoma and carcinoma of other anogential sites; adult T-cell leukemia/lymphoma; gastric carcinoma; cholangiocarcinoma; and urinary bladder cancer. In 2008, approximately 2 million new cancer cases (16%) worldwide were attributable to infection. If these infections could be prevented and/or treated, it is estimated that there would be about 23% fewer cancers in less developed regions of the world, and about 7% fewer cancers in more developed regions. Conclusion: Widespread application of existing public health methods for the prevention of infection, such as vaccination, safer injection practices, quality-assured screening of all donated blood and blood components, antimicrobial treatments, and safer sex practices, including minimizing one's lifetime number of sexual partners and condom use, could have a substantial effect on the future burden of cancer worldwide.